2014
DOI: 10.1155/2014/917981
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide-1 as Predictor of Body Mass Index and Dentate Gyrus Neurogenesis: Neuroplasticity and the Metabolic Milieu

Abstract: Glucagon-like peptide-1 (GLP-1) regulates carbohydrate metabolism and promotes neurogenesis. We reported an inverse correlation between adult body mass and neurogenesis in nonhuman primates. Here we examine relationships between physiological levels of the neurotrophic incretin, plasma GLP-1 (pGLP-1), and body mass index (BMI) in adolescence to adult neurogenesis and associations with a diabesity diathesis and infant stress. Morphometry, fasting pGLP-1, insulin resistance, and lipid profiles were measured in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The primary analysis of the DTI data has been published (23) and the current report comprises a secondary analysis. Data on neurogenesis rates (52), hippocampal volume (16) and amygdala volume (22) have been reported on previously in the identical cohort.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary analysis of the DTI data has been published (23) and the current report comprises a secondary analysis. Data on neurogenesis rates (52), hippocampal volume (16) and amygdala volume (22) have been reported on previously in the identical cohort.…”
Section: Methodsmentioning
confidence: 99%
“…Details for these measurements have been described previously (16, 22, 52). Dentate gyrus neurogenesis was measured at a mean age of 8.7 years whereas volumetric measurements were obtained concomitant to the DTI data (see Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to inducing the expression of growth factors such as Brain‐Derived Neurotrophic Factor (BDNF), which promote neuronal survival (Spielman, Gibson, & Klegeris, ), likewise, it has been observed that incretins prevent neuronal death, and reduce oxidative stress in animals injected with drugs that induce excitotoxicity in the brain (Koshal & Kumar, ). Incretins treatment promotes synaptic plasticity by increasing the number of dendritic spines in regions such as the hippocampus (Coplan et al, ). It also reduces Aβ levels and improves spatial memory.…”
Section: Alzheimer Diseasementioning
confidence: 99%
“…Furthermore, the 8 week administration of liraglutide, an analog of the incretin hormone glucagon-like peptide-1, prevented the decline in hippocampal neurogenesis in a mouse model of AD [ 152 ]. Non-human primates with low body mass index and high GLP-1 levels also tend to have higher hippocampal neurogenesis in comparison to those with high body mass index and low GLP-1 levels [ 153 ]. These studies highlight metabolic hormone influences on adult hippocampal neurogenesis.…”
Section: Introductionmentioning
confidence: 99%